Risk perception and public acceptance toward a highly protested Waste-to-Energy facility. (February 2016) - Ren, Xiangyu; Che, Yue; Yang, Kai; Tao, Yun
Highlights: Analyze the public acceptance of a Waste-to-Energy facility among local residents. Characterize strong protesters by socioeconomic status and geographical distribution. Differentiate the socioeconomic status of protesters and supporters of compensation. Abstract: The application of Waste-to-Energy treatment in Municipal Solid Waste faces strong protest by local communities, especially in cities with high population densities. This study introduces insight into the public awareness, acceptance and risk perception toward Waste-to-Energy through a structured questionnaire survey around a Waste-to-Energy facility in Shanghai, China. The Dichotomous-Choice contingent valuation method was applied to study the willingness to accept of residents as an indicator of risk perception and tolerance. The factors influencing risk perception and the protest response choice were analyzed. The geographical distributions of the acceptance of Waste-to-Energy facility and protest response were explored using geographical information systems. The findings of the research indicated an encouraging vision of promoting Waste-to-Energy, considering its benefits of renewable energy and the conservation of land. A high percentage of protest willingness to accept (50.94%) was highlighted with the effect of income, opinion about Waste-to-Energy, gender and perceived impact. The fuzzy classification among people with different opinions on compensation (valid 0, positive or protest willingness to accept) revealed the existing yet rejected demand of compensation among protesters. Geographical distribution in the public attitude can also be observed. Finally significant statistical relation between knowledge and risk perception indicates the need of risk communication, as well as involving public into whole management process.